2020
DOI: 10.1007/s00520-020-05711-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lipegfilgrastim versus pegfilgrastim in elderly patients with aggressive B cell non-Hodgkin lymphoma (B-NHL): results of the randomized, open-label, non-inferiority AVOID neutropenia study

Abstract: Background Lipegfilgrastim has been shown to be non-inferior to pegfilgrastim for reduction of the duration of severe neutropenia (DSN) in breast cancer patients. This open-label, non-inferiority study assessed the efficacy and safety of lipegfilgrastim versus pegfilgrastim in elderly patients with aggressive B cell non-Hodgkin lymphoma (NHL) at high risk for chemotherapy-induced neutropenia. Patient and methods One hundred and one patients (median age, 75 years) were randomized to lipegfilgrastim or pegfilg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Clinical trials of pegfilgrastim have been shown to have a favourable competence and safety profile for prophylactic usage in patients with cancer receiving chemotherapy and at risk of severe neutropenia and may be preferred by both physicians and patients over short-acting G-CSF due to enhanced adherence and a simple once-per-cycle subcutaneous injection ( 90 92 ). Lipegfilgrastim was found to be an effective option for reducing the duration of severe chemotherapy-induced neutropenia and preventing FN in older patients with aggressive B-cell NHL receiving MSC ( 36 ). Although the current studies published for lipegfilgrastim are still limited, there is an indication that it is a promising treatment for chemotherapy-induced neutropenia.…”
Section: Increasing the Molecular Weight Of G-csf To Extend Its Half-...mentioning
confidence: 99%
“…Clinical trials of pegfilgrastim have been shown to have a favourable competence and safety profile for prophylactic usage in patients with cancer receiving chemotherapy and at risk of severe neutropenia and may be preferred by both physicians and patients over short-acting G-CSF due to enhanced adherence and a simple once-per-cycle subcutaneous injection ( 90 92 ). Lipegfilgrastim was found to be an effective option for reducing the duration of severe chemotherapy-induced neutropenia and preventing FN in older patients with aggressive B-cell NHL receiving MSC ( 36 ). Although the current studies published for lipegfilgrastim are still limited, there is an indication that it is a promising treatment for chemotherapy-induced neutropenia.…”
Section: Increasing the Molecular Weight Of G-csf To Extend Its Half-...mentioning
confidence: 99%
“…This patient group benefits significantly from G-CSF prophylaxis, with a significant 5.7% reduction in the absolute risk of fatal complications after chemotherapy [27]. Dose intensity can be better maintained [29,74].…”
Section: Elderly Patientsmentioning
confidence: 99%